The Hausmann-Gorky effect - Mitu Gulati; Ugo Panizza (Graduate Institute of International and Development Studies, 2018)
For over a century, legal scholars have debated the question of what to do about the debts incurred by despotic governments; asking whether successor non-despotic governments should have to pay them. That debate has gone nowhere. This paper examines whether an Op Ed written by Harvard economist, Ricardo Hausmann, in May 2017, may have shown an alternative path to the goal of increasing the cost of borrowing for despotic governments. Hausmann, in his Op Ed, had sought to produce a pricing penalty on the entire Venezuelan debt stock by trying to shame JPMorgan into removing Venezuelan bonds from its emerging market index. JPMorgan did not comply, but there was a pricing penalty. Intriguingly, the penalty hit only one bond; an issue by Venezuela's state-owned oil company that went on the market two days prior to the Hausmann's piece. That bond then began to carry the name in the market of "Hunger Bond." Using quantitative data and interviews with investors, we try to understand the causes of the Hunger Bond penalty and ask whether there are lessons for policy makers.
Keywords: G15; H63; K34; O54; 330; Venezuela; Odious Debt; Sovereign Default